“We’re all learning together”: exploring peer educator engagement in Recovery Colleges through a participatory research approach - Parsa, Betsabeh; Towle, Angela; Macdonald, Sue (Frontiers in Psychiatry, 2025)
Introduction and purposeRecovery Colleges offer a community-based, recovery-oriented approach that promotes mental health and personal growth through co-produced, peer-led courses. Despite their growth in Canada, limited research examines factors influencing peer educators’ sustained engagement—an essential aspect of program sustainability. This study addresses this gap by identifying key factors and developing best practices to support peer educators in Recovery Colleges and enhance retention and well-being.MethodsThis study employed a mixed-methods Participatory Action Research (PAR) approach, engaging peer educators as co-researchers. A Committee of seven local peer educators (five remained actively involved) co-designed tools and interpreted findings as the advisory peer educators. All Canadian Recovery Colleges were invited to participate. Data were collected from peer educators and program organizers via an online survey and virtual interviews (n=32, across nine provinces). Qualitative data were analyzed using thematic analysis, with coding refined through an iterative process.ResultsWe identified five themes for sustaining peer educator engagement: Inclusivity, Connectedness, Adaptability, Empowerment, and Implementation Factors. Practical recommendations emerged for recruitment, training, and workplace support. The findings emphasize the need for inclusive, adaptable, and empowering environments to sustain peer educator engagement in Recovery Colleges.DiscussionCentring peer educator experiences is critical to upholding Recovery Colleges’ values and creating inclusive, meaningful learning environments that promote personal and community growth. The participatory nature of the research highlighted the unique insights of our advisory peer educators and echoed the Recovery College principles of promoting recovery and building on individual strengths.